2020
DOI: 10.1182/bloodadvances.2020001890
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib induces a dramatic response in a child with refractory juvenile xanthogranuloma with a novel MRC1-PDGFRB fusion

Abstract: Key Points Juvenile xanthogranuloma (JXG) usually presents with lesions isolated to the skin; however, aggressive, disseminated forms also occur. Identification of a novel MRC1-PDGFRB fusion in a child with JXG guided targeted therapy with dasatinib, leading to a dramatic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…We are aware of only one previous case report describing cyclin D1 staining in XG, where it was suggested to be a surrogate marker for RTK mutation in a case of aggressive, disseminated XG. 24 Because cyclin D1 protein is transcriptionally regulated by numerous signaling pathways, its expression may suggest that at least one of these pathways is aberrantly activated. Approximately 75% of XG lesions, including localized cutaneous lesions, showed activating RTK/MAPK mutations or gene fusions in a recent study by Durham et al 13 Eighty percent of the lesions in our limited study showed strong and diffuse staining for cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of only one previous case report describing cyclin D1 staining in XG, where it was suggested to be a surrogate marker for RTK mutation in a case of aggressive, disseminated XG. 24 Because cyclin D1 protein is transcriptionally regulated by numerous signaling pathways, its expression may suggest that at least one of these pathways is aberrantly activated. Approximately 75% of XG lesions, including localized cutaneous lesions, showed activating RTK/MAPK mutations or gene fusions in a recent study by Durham et al 13 Eighty percent of the lesions in our limited study showed strong and diffuse staining for cyclin D1.…”
Section: Discussionmentioning
confidence: 99%
“…Histiocytic disorders usually involve a single somatic alteration; however, genomic studies on histiocytoses have showed an increasing number of gene fusions involving NTRK1, BRAF, RET, and ALK. 3,5,16 Although there is a shared understanding of the histopathology of NLCH, the molecular characterization is not fully elucidated. Evaluation of this patient will include ongoing management with hematology and oncology as a result of ANKRD26-mutation-associated risk for myeloid malignancies.…”
Section: Lab Resultsmentioning
confidence: 99%
“…4 In general, malignant systemic NLCH has a poor prognosis, on the other hand cutaneous NLCH usually is benign with a good prognosis and likelihood of spontaneous regression. 5 However, some reported cases of cutaneous NLCH may progress rapidly and require systemic therapy. 6 Approximately 10% of adults with non-LCH will have concomitant myeloid neoplasms, which may also exhibit BRAF mutations and in turn, require targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Recently, disseminated JXG with specific genetic mutations have been targeted with tyrosine kinase inhibitors. 19 The overall prognosis of JXG is good but a high degree of morbidity and mortality is associated with disseminated JXG in infants with extensive visceral involvement. 10 Our patient showed gradual spontaneous regression of lesions and their growth was negligible compared with the relative growth of the patient, by 6 months of age (►Fig.…”
Section: Discussionmentioning
confidence: 99%